Tolosa-Hunt Syndrome in Childhood and Adolescence: A Literature Review in the Last 10 Years - Gama, Bárbara Pinheiro; Silva-Néto, Raimundo Pereira (Neuropediatrics, 2020)
Objectives The aim of the study is to review the articles published in the last 10 years on Tolosa-Hunt syndrome (THS) in childhood and adolescence to learn about its clinical and epidemiological characteristics and its therapeutic management.Methods Based on the literature search in the major medical databases and using the descriptors “Tolosa-Hunt syndrome and children” and “Tolosa-Hunt syndrome and adolescent” we included articles published between 2009 and 2019. We found 51 articles, but only 11 met the inclusion criteria.Results There were eight women and four men with THS, whose average age was 12.0 ± 4.3 years, ranging from 4 to 17 years. Magnetic resonance imaging showed inflammation in the cavernous sinus (100%), orbit (25%), and superior orbital fissure (8.3%), unilateral in all patients. The internal carotid artery (58.3%), third (66.7%), sixth (33.3%), and fourth (25%) cranial nerves were injured. Headache was located in the orbital region, ipsilaterally to nerve involvement and had mild to severe intensity. Corticosteroid was the treatment used in 91.7% of the patients. They were followed for an average of 13.4 ± 12.4 months. Only two patients had recurrence of the disease.Conclusion THS is infrequent in childhood and adolescence and knowledge of its clinical and epidemiological characteristics and its therapeutic management is necessary for pediatricians.
Keywords: Tolosa-Hunt syndrome; cavernous sinus; cranial nerves; childhood; adolescence